2007
DOI: 10.1002/adfm.200600624
|View full text |Cite
|
Sign up to set email alerts
|

“Solvent Annealing” Effect in Polymer Solar Cells Based on Poly(3‐hexylthiophene) and Methanofullerenes

Abstract: The self‐organization of the polymer in solar cells based on regioregular poly(3‐hexylthiophene) (RR‐P3HT):[6,6]‐phenyl C61‐butyric acid methyl ester (PCBM) is studied systematically as a function of the spin‐coating time ts (varied from 20–80 s), which controls the solvent annealing time ta, the time taken by the solvent to dry after the spin‐coating process. These blend films are characterized by photoluminescence spectroscopy, UV‐vis absorption spectroscopy, atomic force microscopy, and grazing incidence X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
936
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,139 publications
(971 citation statements)
references
References 45 publications
(66 reference statements)
31
936
3
1
Order By: Relevance
“…48 Li et al used a slow drying process to control the P3HT crystallization and phase separation. 64,65 They found that P3HT was better ordered, as evidenced by the enhanced absorption. By using time-of-flight mobility measurements, a more balanced charge transport was also obtained for the slow-dried samples.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%
“…48 Li et al used a slow drying process to control the P3HT crystallization and phase separation. 64,65 They found that P3HT was better ordered, as evidenced by the enhanced absorption. By using time-of-flight mobility measurements, a more balanced charge transport was also obtained for the slow-dried samples.…”
Section: Thermal Annealing Approachmentioning
confidence: 99%
“…[20]. The photoactive layers were "solvent annealed" overnight and dried at 110 °C for 10 min according to [97]. Thickness of the P3HT/PCBM layer was ~120 nm.…”
Section: Cnts For Organic Solar Cellsmentioning
confidence: 99%
“…Following exciton dissociation the free carriers must have contiguous percolation pathways to drift/diffuse towards the collection electrodes, a process which is favoured by larger sized domains. Processing methods such as thermal, 2 solvent, 3 annealing, and solvent additives 4 improve device efficiency by modifying the active layer morphology. Transmission electron microscopy (TEM) is an ideal technique for probing morphology at nanometre length scales, but in the case of BHJ solar cells imaging is complicated by the low contrast between the carbon-rich donor and acceptor phases.…”
mentioning
confidence: 99%